Current infant feeding practices and impact on growth in babies during the second half of infancy. Issue 4 (30th June 2014) - Bandara, T.; Hettiarachchi, M.; Liyanage, C.; Amarasena, S.
Abstract Background Sri Lanka has made remarkable improvements in health, social and educational indices. However, child malnutrition exists as a significant health problem. Infant feeding indicators have not reached expected levels and improvements are partly constrained by a lack of data. The present study aimed to determine current infant feeding practices and their impact on growth among 6–12‐month‐old infants. Methods The study comprised a descriptive cross‐sectional investigation conducted in randomly selected (n = 7) Public Health Midwife areas in Galle, Sri Lanka. An interviewer‐administered questionnaire was used to obtain data on sociodemographics and infant feeding. Mothers (n = 515) attending well‐baby clinics were recruited on voluntary and consecutive basis. Infants' body weights and lengths were measured using standard procedures. Results Exclusive breastfeeding rate for first 6 months was 49.0%. In total, 42.6% infants (219 out of 515) were given rice as first weaning food, followed by salt (58.6%) and sugar (42.3%). Oil had been introduced to 84.9% of infants by the end of 12 months. Most infants (over 71%) were given dairy products, whereas 62.3% were being fed various liquid foods using bottles. The introduction of commercial infant cereals, chocolates, plain tea, ice cream and deep fried snacks was noted. Age‐specific body weight and length were not achieved by 30.5% and 29.5% of infants, respectively. Weight for length was not achieved by 25.5% of the infants. Delayed achievements of motor milestones were observed. Mothers' knowledge scores on basic nutrients were low. Conclusions Complementary feeding indices of the study group were not satisfactory. Maternal and child healthcare personnel need to identify causative factors for inappropriate feeding with a view to improve the complementary feeding patterns.